Stabilisasi Tanah Lempung Ekspansif dengan Limbah Keramik: Studi Kasus: Tanah di Tanete, Lembang Limbong, Kecamatan Rembon, Kabupaten Tana Toraja - Parea Rusan Rangan; Abdias Tandy Arrang (Publikasi dan UKI Press UKI Toraja., 2020)
Expansive clay is a soil that has high fluctuation of shrinkage and contains minerals that have a high potential to expand when exposed to water, so this type of soil requires special handling so that it can be used as a basis for construction. One effort that can be used to improve the soil is by stabilizing the soil by adding other materials, namely ceramic waste. Ceramic waste is an unused residual material that is usually found in building construction. This study aims to determine the effect of ceramic waste in stabilizing and increasing the bearing capacity of expansive clay with the percentage of adding ceramic waste to expansive clay, namely: 0%, 5%, 10%, 15%. The location for taking ceramic waste is in Rembon, Tana Toraja district and for expansive clay taking is in Tanete, Rembon District, Tana Toraja Regency. The test was carried out at the civil engineering laboratory of the Christian University of Indonesia Toraja. From the CBR (California Bearing Ratio) test, it was obtained for native soil (0%) = 1.12%, and for the addition of ceramic waste (5%) = 2.10%, for (10%) = 4.03%, for (15%) = 6.09% . The results showed that the addition of ceramic waste could increase the bearing capacity of expansive clay.Keywords: Expansive Clay Soil, Soil Stability, Ceramic Waste.